Differential drug retention between anti-TNF agents and alternative biological agents after inadequate response to an anti-TNF agent in rheumatoid arthritis patients. Issue 6 (30th January 2012) - Du Pan, Sophie Martin; Scherer, Almut; Gabay, Cem; Finckh, Axel
Abstract : Background: After inadequate response to an antitumour necrosis factor (aTNF) agent for treatment of rheumatoid arthritis (RA), rheumatologists can choose an alternative aTNF or a biological agent with another mode of action (non-aTNF biological (non-aTNF-Bio)). Objective: To compare drug retention rates of non-aTNF-Bio with alternative aTNF. Methods: All patients within the Swiss RA cohort (SCQM-RA) treated with an alternative biotherapy after a prior inadequate response to aTNF were analysed. The drug retention of alternative aTNF was compared with non-aTNF-Bio using Cox proportional hazards models, adjusted for potential confounders. Results: 1485 treatment courses after aTNF failure were available for analysis, 853 with alternative aTNF and 632 with non-aTNF-Bio. The median drug retention was 32 months (IQR 14–54) on non-aTNF-Bio versus 21 months (IQR 8–53) on alternative aTNF, or a 50% reduction drug discontinuation risk in favour of non-aTNF-Bio (adjusted hazard ratio (HR) for non-aTNF-Bio: 0.50 (95% CI 0.41 to 0.62)). This effect appears to be modified by the type of prior aTNF failure, with a larger difference in favour of non-aTNF-Bio in patients having experienced a primary failure with a previous aTNF (HR: 0.33 (95% CI 0.24 to 0.47), p<0.001). Conclusion: After inadequate response to aTNF, and particularly after primary failure, patients on a non-aTNF-Bio agent have significantly higher drug retention rates.